Enhancing mathematical problem-solving skills through problem-based learning with Liveworksheets assistance - Mahfudhoh, Anggraeni Al; Andrijati, Noening (Indonesian Journal of Science and Mathematics Education, 2024)
This study examines and analyzes differences in mathematical problem-solving abilities among students taught using Problem-based Learning (PBL) with Liveworksheets assistance and those taught using conventional learning models supported by worksheets on the division topic. The research employed a quasi-experimental design involving 185 fourth-grade elementary school students. Samples were selected using simple random sampling, resulting in 66 students as participants. Data were collected through tests and documentation. The findings reveal a significant improvement in problem-solving skills among students taught using the PBL model with Liveworksheets assistance, evidenced by a higher N-gain score of 0.70 compared to the control group's score of 0.42. Thus, integrating Liveworksheets into PBL effectively enhances students' mathematical problem-solving abilities. This study implies innovative technology-assisted learning models can significantly improve mathematics learning outcomes.